„Эпитафия Владимиру Высоцкому” Яцека Качмарского как интертекст - Osiewicz, Bartosz (My University, 2011)
This article is devoted to the analysis of the poem Epitafium dla Włodzimierza Wysockiego (Epitaph for Vladimir Vysotsky) of Jacek Kaczmarski. In this poem the Polish bard conducts an intertextual dialogue with outstanding Russian poet and singer Vladimir Vysotsky.
The analysis of the poem „Epitaph for Vladimir Vysotsky” of Jacek Kaczmarski as intertext
„Epitafium dla Włodzimierza Wysockiego” Jacka Kaczmarskiego jako intertekst